Collaborative Control of Multimotor Systems for Fixed-Time Optimisation Based on Virtual Main-Axis Speed Compensation Structure - Changfan Zhang; Mingjie Xiao; Jing He; Zhitian Liu; Xingxing Yang; Qian Zhang; Hongrun Chen (Complexity)
In response to the high-speed and high-precision collaborative control requirements of the multimotor system for filling, a new type of virtual master-axis control structure is proposed and a multimotor fixed-time optimized collaborative control algorithm is designed. Firstly, coupling relationship between virtual and slave motors is effectively established by designing a velocity compensation module for the virtual motor. Secondly, the sliding mode observer (SMO) is used to reconstruct the composite disturbance composed of motor parameter perturbation and load disturbance. Finally, the variable gain terminal sliding mode controller (SMC) is designed to ensure that each slave motor can track the given value within a fixed time. The fast convergence of the system can be proved by the fixed-time convergence theorem and Lyapunov’s stability theorem. The simulation results show that, compared with the traditional virtual main-axis control strategy, the proposed method is more effective for the tracking control of each slave motor in the initial stage.